Analisis Sanitasi Lingkungan Fisik Rumah Pada Kejadian Demam Berdarah Dengue (DBD) Di Wilayah Kerja Puskesmas Bentiring Kota Bengkulu - Mely Gustina; Deltavia Meilanda (Jurnal Sanitasi Profesional Indonesia, 2026)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus infection, characterized by hemorrhagic symptoms that may lead to shock and death. One of the causes of dengue outbreaks is poor environmental sanitation. Environmental sanitation factors play an important role in the spread of DHF. The purpose of this study is to analyze the physical environmental sanitation of households with a history of DHF in the working area of Bentiring Public Health Center, Bengkulu City, which includes the physical condition of the house (screened ventilation, lighting, temperature, and humidity), water storage conditions, and waste disposal systemsMethod: The research method used was a descriptive approach, providing detailed descriptions. Based on observations, most houses did not meet proper environmental sanitation standards to prevent the breeding of Aedes aegypti mosquitoes.Results: All houses had ventilation, but only 12.5% were equipped with protective screens. A total of 62.5% of houses had lighting below the standard (less than 60 lux). In terms of temperature, 75% of houses had ideal conditions, ranging from 18°C to 30°C. Air humidity in 62.5% of houses did not meet the standard as it was above 60%. In addition, water storage conditions and waste disposal systems were also categorized as poor, reaching 100%. It is recommended that the community increase awareness of the importance of maintaining a healthy home environment, such as installing wire screens on ventilation, ensuring proper lighting, temperature, and humidity, as well as regularly practicing the 3M Plus program. Furthermore, waste disposal should be carried out properly and regularly. The government and health workers are also advised to continuously provide education and conduct regular sanitation monitoring in dengue-prone areas